Pathways to a diagnosis of trigeminal neuralgia: a qualitative study of patients’ experiences - Cameron Werner; Jeni Harden; Julia Lawton (BMC Primary Care)
Abstract Background Trigeminal Neuralgia (TN) is a rare disorder which causes episodes of intense facial pain and has been described as the ‘suicide disease’. Hence, prompt diagnosis and timely initiation of treatment is vital. However, delays to diagnosis and high rates of misdiagnosis are common, particularly within primary care. To date, most research has focused upon treatment options rather than improving diagnostic experiences. This study sought to explore patients’ experiences of the events leading up to their TN diagnosis and their views about the care and support they received when they were diagnosed to provide recommendations for improving the TN diagnostic pathway. Methods This was a qualitative, exploratory study using in-depth interviews. Interviews were conducted with (n = 25) UK-based people with TN recruited via online forums. Data were analysed thematically. Results Following the onset of their TN pain, most participants described an arduous and uncertain journey to diagnosis, with many encountering significant delays, misdiagnoses and receiving inappropriate referrals and treatment. As a consequence, participants reported experiencing profound distress, anxiety, depression and, in extreme cases, suicidal ideation; some also described drug and alcohol misuse during this time. Most participants conveyed relief upon finally receiving a diagnosis. However, this was often by eclipsed by what they saw as poor and insensitive communication and inadequate information provisioning. Conclusions The present study highlights the importance of developing bespoke training for primary care and other professionals to facilitate timely recognition of TN symptomatology and ensure that they deliver a TN diagnosis in clear, sensitive and empathetic ways.